Diversity in Intercultural Educational Reforms - Hector Muñoz Cruz (Universidad Autónoma de Baja California, 2002)
This study analyzes the implications of contemporary linguistic and cultural diversity concerning educational theory from three different perspectives: intercultural bilingual-education proposals; the demographical view in relation to language distribution and functionality; and the analysis of diversity within the framework of linguistic and cultural conflict. In recent searches for the meanings of diversity, sociolinguistic investigations have postulated that the consequences of the loss of diversity and its replacement by uniformity will be reflected in three important dimensions of social life: first, changes in communicative function and in cultural continuity; second, a more intense concentration of rationality or reflection on dominant linguistic and cultural models; and third, an intensification of the processes of diversification and specialization of subjects' cultural skills pertaining to the needs of global projects. Multiculturalism and inequalities have erupted with such an impact on the sociopolitical platforms of global, national and ethnic projects that they have changed diversity and multidirectionality into fascinating but conflictive disclosures. Little by little these notions are giving support to a citizenship parameter for the society of the near future, when new national problems will arise, and new solutions, charged with participation and democratic meaning, will have to be devised. At the moment, the phenomena of interculturality, bilingualism and ethnodiversity are creating new parameters for the discussion of educational reform.